Development and Validation of a Survey on Inclusive Judo: Judo Teachers’ Attitudes Towards Including Participants with Intellectual Developmental Disorders (J-TAID) - Gaston Descamps; Alain Massart; Terry Rizzo; Viktorija Pečnikar Oblak; Maria João Campos (Sports)
This study developed and refined the Judo Teachers’ Attitudes Towards Including Participants with Intellectual Developmental Disorders (J-TAID) survey, addressing the need to assess attitudes, subjective norms, perceived behavioral control, and intention regarding inclusion, and grounded in the Theory of Planned Behavior. The survey, translated into English, Portuguese, French, and Slovenian, was administered to 163 participants in order to assess its reliability and validity using Cronbach’s alpha, Principal Component Analysis (PCA), Confirmatory Factor Analysis (CFA), and Exploratory Factor Analysis (EFA). Internal consistency regarding attitudes, subjective norms, and perceived behavioral Constructs ranged from 0,79 to 0.80, with test–retest reliability improving, demonstrating moderate to strong temporal stability (α = 0.679–0.813). The PCA and CFA identified a robust three-factor structure explaining 74% of the variance, with good model fit (RMSEA = 0.048, CFI = 0.978). Pearson correlations supported the TPB constructs. The refined J-TAID demonstrates validity and reliability for its intended purpose, although the results are still preliminary, and the limitations that were observed suggest a need for further validation.